2013
DOI: 10.4081/mrm.2013.573
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and carotid intima-media thickness in chronic obstructive pulmonary disease

Abstract: Background: The aim of this study is to investigate the prevalence of metabolic syndrome (MetS), carotid intima media thickness (IMT), and serum C-reactive protein (CRP) levels in patients with chronic obstructive pulmonary disease (COPD), and the possible relationships among them. Methods: Fifty stable COPD patients and 40 healthy controls were included in the study. The participants were further divided into four groups according to their smoking status. Pulmonary function tests were performed in COPD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
1
11
1
1
Order By: Relevance
“…In addition, results of the present work revealed that, COPD with metabolic syndrome was significantly prevalent in females, subjects with significantly higher body mass index and FEV1%. These results were agreed with previous trials showed that, COPD subjects with metabolic syndrome were more frequently females, with higher BMI and FEV1% compared to COPD patients without metabolic syndrome [18][19][20] . In addition, Cebron Lipovec et al [17] reported that, patients with metabolic syndrome in addition to COPD had higher body mass index, with high forced expiratory volume in one second predicted and were more prevalent in females.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, results of the present work revealed that, COPD with metabolic syndrome was significantly prevalent in females, subjects with significantly higher body mass index and FEV1%. These results were agreed with previous trials showed that, COPD subjects with metabolic syndrome were more frequently females, with higher BMI and FEV1% compared to COPD patients without metabolic syndrome [18][19][20] . In addition, Cebron Lipovec et al [17] reported that, patients with metabolic syndrome in addition to COPD had higher body mass index, with high forced expiratory volume in one second predicted and were more prevalent in females.…”
Section: Discussionsupporting
confidence: 93%
“…40 Subsequent study from Netherland reported that mean BMI in COPD group and control group were 26.2±5.1 kg/m 2 and 27.3±4.2 kg/m 2 respectively. 28 Bulcun E et al, found BMI in COPD patients 26.3±4.8 kg/m 2 but in control it was 28.1±3.7 kg/m 2 in their study. 38 Prevalence of Metabolic Syndrome in the study was 31.34%.…”
Section: Resultsmentioning
confidence: 60%
“…(Comparison of various parameters are given in (Table 2 and Table 3). 28 Bulcun E et al, had found mean age in their study 63.10±9.6 years, while in control population it was 60.9±10.6. 38 Mekov E et al, in their study had observed, mean age of patients was 65±10 years in which 71.1% were males, 28.9% were females.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations